(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article considers the pragmalinguistic features of the periphrases used in the modern media space. Despite the richness and fertility of the Kazakh language, members of society, in order to convey their thought as briefly as possible, tend to use borrowed words in their speech. This process has a negative impact on both the thinking system and the general culture of a person. Therefore, in everyday life, it is necessary to widely promote the use of figurative expressions that reflect the artistic competence of our native language, in particular, the use of paraphrases that have a special place. The implementation of the above task can be rationally and easily carried out through the mass media, which occupy a reliable place in all spheres of public life. In this regard, the topic of the author of the article, who has set the goal of giving a semantic pragma linguistic analysis of the periphrasis of the modern media text, is relevant, and the given facts are valid and realistic. The main objects of research in the field of linguo-pragmatics are media texts of various subjects published in modern Kazakh-language media. The author classifies fragments of media texts used in peripheral units, collected from publications and websites familiar to the modern readers of Kazakhstan, in relation to a number of areas of public life. The ability to use appropriately and effectively the rich vocabulary of the native language to convey the final pragmatic position of the author of the media text is an interesting and complex task that requires a great responsibility from the researcher. The applicant aims to meet such a high standard and to use the latest research in the field of linguistics. Keywords: periphrasis; media text; social status; linguopragmatics.